Characterization of salt tolerance and Fusarium wilt resistance of a sweetpotato mutant - Huan ZHANG; Qian ZHANG; Yan-nan WANG; Yan LI; Hong ZHAI; Qing-chang LIU; Shao-zhen HE (Journal of Integrative Agriculture, 2017)
The variant LM1 was previously obtained using embryogenic cell suspension cultures of sweetpotato variety Lizixiang by gamma-ray induced mutation, and then its characteristics were stably inherited through six clonal generations, thus this mutant was named LM1. In this study, systematic characterization of salt tolerance and Fusarium wilt resistance were performed between Lizixiang and mutant LM1. LM1 exhibited significantly higher salt tolerance compared to Lizixiang. The content of proline and activities of superoxide dismutase (SOD) and photosynthesis were significantly increased, while malonaldehyde (MDA) and H2O2 contents were significantly decreased compared to that of Lizixiang under salt stress. The inoculation test with Fusarium wilt showed that its Fusarium wilt resistance was also improved. The lignin, total phenolic, jasmonic acid (JA) contents and SOD activity were significantly higher, while H2O2 content was significantly lower in LM1 than that in Lizixiang. The expression level of salt stress-responsive and disease resistance-related genes was significantly higher in LM1 than that in Lizixiang under salt and Fusarium wilt stresses, respectively. This result provides a novel and valuable material for improving the salt tolerance and Fusarium wilt resistance of sweetpotato.